Anderson localization and Brewster anomalies in photonic disordered quasiperiodic lattices (2011)
ABSTRACT: A comprehensive study of the properties of light propagation through one-dimensional photonic disordered quasiperiodic superlattices, composed of alternating layers with random thicknesses of air and a dispersive metamaterial, is theoretically performed. The superlattices consist of the successive stacking of N quasiperiodic Fibonacci or Thue-Morse heterostructures. The width of the slabs in the photonic superlattice may randomly fluctuate around its mean value, which introduces a structural disorder into the system. It is assumed that the left-handed layers have a Drude-type dispersive response for both the dielectric permittivity and magnetic permeability, and Maxwell’s equations are solved for oblique incidence by using the transfer-matrix formalism. The influence of both quasiperiodicity and structural disorder on the localization length and Brewster anomalies are thoroughly discussed.